2017
DOI: 10.1016/j.rbmo.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Multifetal reduction of triplets to twins compared with non-reduced twins: a meta-analysis

Abstract: The current systematic review and meta-analysis evaluates the perinatal outcomes in twin pregnancies following multifetal pregnancy reduction (MPR) compared with non-reduced twins. We considered all studies comparing perinatal outcomes of twin pregnancies following MPR to non-reduced twin pregnancies. Our search yielded 639 publications, of which 91 were assessed for eligibility. A total of 22 studies met our inclusion criteria. Overall, fetal reduction of triplets to twins resulted in comparable perinatal out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Importantly, twins reduced to singletons did not increase pregnancy loss at <24 weeks. These findings are consistent with previous studies (26) (27), which suggest that MFPR from twins to singletons has a clear advantage for twin pregnancies. The conclusion can be drawn from previous studies and the present study that MFPR improves the outcomes of triplet or twin pregnancies.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, twins reduced to singletons did not increase pregnancy loss at <24 weeks. These findings are consistent with previous studies (26) (27), which suggest that MFPR from twins to singletons has a clear advantage for twin pregnancies. The conclusion can be drawn from previous studies and the present study that MFPR improves the outcomes of triplet or twin pregnancies.…”
Section: Discussionsupporting
confidence: 93%
“…In a meta‐analysis by Zipori et al, a comparable perinatal outcome was found between the FR group and the nonreduced DCDA twin's group in terms of prematurity rate before 28, 32, or 36 weeks, fetal weight, pregnancy loss before 24 weeks, and the development of gestational diabetes and hypertension disorders. The only difference in the analysis was the significantly higher cesarean section rate in the FR group compared to the non‐reduced DCDA twin group 23 . Kim et al compared the results of 59 DCDA twins who had a fetal reduction and 157 DCDA twins who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Overall rates of pregnancy loss after multifetal reduction procedure are low and comparable to rates of loss with expectant management of a multifetal gestation. [26][27][28] Although preterm labor and pregnancy loss postprocedure are more commonly related to spontaneous rupture of membranes, infection has been described as an uncommon complication of reduction that may be associated with untimely fetal loss. 29 While chorionic villous sampling also carries a rare risk of procedurerelated infection, 30,31 the prolonged time interval from sampling procedure at 14 weeks to clinical symptoms at 17 weeks precludes this possibility in this case.…”
Section: Discussionmentioning
confidence: 99%